2008
DOI: 10.1590/s1516-93322008000400003
|View full text |Cite
|
Sign up to set email alerts
|

Hormônio do crescimento e exercício físico: considerações atuais

Abstract: Embora o hormônio do crescimento (GH) seja um dos hormônios mais estudados, vários de seus aspectos fisiológicos ainda não INTRODUÇÃOA importância dos hormônios no controle do metabolismo corporal é fato conhecido há bastante tempo. Dentre os hormônios mais estudados pela ciência está o hormônio do crescimento (GH) (Lange, 2004;Doessing, Kjaer, 2005). Alguns aspectos fisiológicos, contudo, ainda permanecem controversos e desconhecidos, incluindo fatores que regulam sua síntese, mecanismos de ação e efeitos no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
29

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 87 publications
0
7
0
29
Order By: Relevance
“…Adult individuals, when subjected to interventions for weight reduction usually have fat mass reduction with concomitant reduction of lean mass 23 , however, in adolescents, reducing body fat, arising interventions with moderate energy deficit, isn´t accompanied by a reduction in lean body mass 12 , probably because the adolescence be a highly anabolic phase due to the high concentration of circulating anabolic hormones such as growth hormone (GH). 24 In this intervention, it was observed that the control group also showed improvements in body shape after 12 weeks of aerobic training.…”
Section: Discussionmentioning
confidence: 86%
“…Adult individuals, when subjected to interventions for weight reduction usually have fat mass reduction with concomitant reduction of lean mass 23 , however, in adolescents, reducing body fat, arising interventions with moderate energy deficit, isn´t accompanied by a reduction in lean body mass 12 , probably because the adolescence be a highly anabolic phase due to the high concentration of circulating anabolic hormones such as growth hormone (GH). 24 In this intervention, it was observed that the control group also showed improvements in body shape after 12 weeks of aerobic training.…”
Section: Discussionmentioning
confidence: 86%
“…In relation to a reduction in serum levels of GH in the SO group, a study [36] explains why athletes usually have lower GH release induced by exercise in sedentary or poorly trained individuals; Silva and Lengyel [37] in their studies, demonstrated that the synthesis of GH is also regulated by negative feedback. In other words, the high concentration of GH in circulation may lead to reduced stimulation of its synthesis in the adenohypophysis and/or reduced interaction with their receptors in body tissues, thus, attenuating its effects.…”
Section: Citationmentioning
confidence: 99%
“…According to Cruzat et al, (2008), in skeletal muscle, GH has an anabolic effect on protein synthesis, and it is for this reason that physical activity and muscular strength training (ST) produce increased muscle mass, a process called "hypertrophy".…”
Section: Introductionmentioning
confidence: 99%